Peningkatan Kompetensi Guru dalam Otomatisasi Instrumen Evaluasi Pembelajaran Melalui Pelatihan Google Apps Script (GAS) dan Integrasinya dengan Google Form - Sari, Arnida; Azmi, Memen Permata; Granita, Granita; Muhandaz, Ramon (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
The challenges of learning evaluation in the digital era demand efficiency and personalization. Google Forms (GF), although popular, has limited functionality when it comes to advanced automation, such as certificate creation, access restrictions, and complex notifications. This training aims to improve teachers' competency in utilizing Google Apps Script (GAS) to automate and develop GF-based learning evaluation instruments. The method used is Participatory Action Learning (PAL), which includes pre-tests, material delivery (lectures, demonstrations), independent practice, and post-tests. The results of the community service show significant improvements in teachers' understanding and skills in writing simple scripts, integrating GAS with GF and Google Sheets, and successfully creating automation solutions such as a system for sending quiz feedback and issuing digital certificates in real time. This increased competency has a direct impact on work efficiency and the quality of evaluation services to students.